2006
DOI: 10.2961/jlmn.2006.01.0008
|View full text |Cite
|
Sign up to set email alerts
|

Surface Micro-Structuring of Silica Glass by Laser-Induced Backside Wet Etching with ns-Pulsed UV Laser at a High Repetition Rate

Abstract: We have been studying the refractive index changes and vacancies that are induced in transparent materials like glass by the irradiation of femtosecond laser pulses. This technique has been applied to fabricate three-dimensional photonic structures such as optical data storages, waveguides, gratings, and couplers inside a wide variety of transparent materials. We report micro-fabrication experiments of optical elements in glasses with femtosecond laser pulses, including fabrication of couplers, Bragg gratings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…New recording techniques are therefore being examined, such as ultrashort pulsed-laser illumination using a femto-second laser [6]. Laser-induced backside etching using a nanosecond-pulsed laser scan has also been reported for inscribing the grating on the silica glass [7]. Moreover, Nastas et al reported a holographic recording technique for chalcogenide glass using laser irradiation in conjunction with a corona discharge [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…New recording techniques are therefore being examined, such as ultrashort pulsed-laser illumination using a femto-second laser [6]. Laser-induced backside etching using a nanosecond-pulsed laser scan has also been reported for inscribing the grating on the silica glass [7]. Moreover, Nastas et al reported a holographic recording technique for chalcogenide glass using laser irradiation in conjunction with a corona discharge [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Laser-induced backside wet etching (LIBWE) was invented a decade ago [1]. Several types of UV laser have been utilized, including excimer lasers [2][3][4][5][6][7], hybrid feedbackdistributed dye/excimer lasers [8], and Q-switched solid state lasers [9][10][11][12]. More recently, a visible laser source [13,14] and a near-IR laser source [15] have also been used.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular technologies are laser-induced backside wet etching (LIBWE) [16,[19][20][21][22], laser-induced backside dry etching (LIBDE) [17,18,23], laser induced plasma assisted ablation (LIPAA) [24][25][26], and lased-induced black-body heating (LIBBH). The last one has been developed at Laser Technology Department of ITMO University [27][28][29][30][31].…”
Section: ключевые слова: Fused Silica Microstructuring Microlens Arrmentioning
confidence: 99%